Sociodemographic and clinical profile of bone marrow transplant recipients: Reference Centers in Brazil and Spain (Research, Society and Development, 2020)
To characterize the sociodemographic and clinical profile of Bone Marrow Transplant in two centers in Brazil and one in Spain. Cross-sectional study conducted with 40 respondents appropriate to the inclusion criteria. Data were collected from March 2016 to October 2017.  We found a differentiation of gender and age group between countries: predominance of females (25%); age group from 21 to 50 years (30%) in Brazil and male (37.5%); age group 51 to 70 years (35%) in Spain. There was similarity, respectively, of race / white color, 1st grade education, married marital status, Catholic religion, income from 1 to 2 minimum wages, primary disease and leukemia. highest frequency of Halogen transplantation in Spain (37.5%). The study had a strengthening advance in nursing actions, providing them with tools for organization, planning and decision making, and for promoting care with patients and their families.